An upgraded method to relocate marked shoots of the seagrass Zostera marina - Solana-Arellano, Elena (Universidad de Costa Rica, 2000)
This paper presents a new method for the recovery of marked seagrass blades. The introduction of a plastic belt surrounding the marked shoot at a sediment level provided a relocation arrangement which was unloosed by drag forces or grazing. The relocation method was tested on Zostera marina L. It proved to have the advantage of increasing dramatically the number of marked shoots recovered up to 100% while reducing the cost of the procedure to a minimum. An allometric model indicated that the introduced relocation method has no impact on the development of the plant.